IMPROVING ELEMENTARY SCHOOL TEACHERS’ COMPETENCE THROUGH THE NUMBERED HEAD TOGETHER METHOD AT SD OF TAMBANG SUB-DISTRICTS IN KAMPAR - Endang Purwanti (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2023)
This paper reports the improvement of teacher competence in a teacher work programme at elementary schools in the Tambang Sub-District, Kampar, through the Numbered Heads Together method based on the background of the problem. Hence, the formulation of the problem is: “Can the Numbered Heads Together method increase elementary school teacher competence at SD Tambang Sub-District in Kampar?” The research employed a School Action Research (SAR) design using the Kemmis and McTaggart model, which follows a spiral cycle from one phase to the next. The research subjects were elementary school teachers in the Tambang Sub-District of Kampar. The number of classroom teachers involved as research subjects was 12, along with school principals at SD in the Tambang Sub-District of Kampar. Based on the results of the analysis and discussion, it can be concluded that the Numbered Heads Together method can improve teacher competence. Through the implementation of the Numbered Heads Together method, teachers’ activities became more active, and teachers tended to show positive attitudes in participating in the teaching and learning process conducted by the researcher. In Cycle I, the teachers’ teaching competence was categorized as good, with an average score of 70.29. Meanwhile, in Cycle II, the teachers’ teaching competence increased to an average score of 79.52, which was classified as very good.